2020
DOI: 10.1016/j.gore.2019.100526
|View full text |Cite
|
Sign up to set email alerts
|

Development of localized cul-de-sac endometrioid carcinoma associated with deep infiltrating endometriosis during remission of early endometrial cancer

Abstract: HighlightsA cul-de-sac endometrioid carcinoma adjacent to extraovarian endometriosis was identified during remission of endometrial cancer.The origin of the cul-de-sac tumor was malignant transformation of deep infiltrating endometriosis.Endometriosis-related cancer was identified in a woman with endometrial cancer during remission.Hyperestrogenism due to infertility treatment may contribute to malignant transformation of deep infiltrating endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Ferrari et al 14 reported a case of clear cell carcinoma in a parietal endometriosis lesion (post‐cesarean section and transverse laparotomy), while Chen et al 15 reported two cases of high‐grade serous cancer (HGSC) in an endometriosis of the utero‐sacral ligament, followed by Johnson et al 16 and Song et al, 17 each of whom reported a case of HGSC from in a rectal endometriosis. If we add the cases of cervical and rectal degeneration associated with Lynch syndrome, 18 and vaginal degeneration associated with endometrial cancer, 19 , 20 there are less than 10 cases of degeneration described in the literature (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ferrari et al 14 reported a case of clear cell carcinoma in a parietal endometriosis lesion (post‐cesarean section and transverse laparotomy), while Chen et al 15 reported two cases of high‐grade serous cancer (HGSC) in an endometriosis of the utero‐sacral ligament, followed by Johnson et al 16 and Song et al, 17 each of whom reported a case of HGSC from in a rectal endometriosis. If we add the cases of cervical and rectal degeneration associated with Lynch syndrome, 18 and vaginal degeneration associated with endometrial cancer, 19 , 20 there are less than 10 cases of degeneration described in the literature (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most malignant tumors arising from endometriosis are derived from the ovarian endometrioma. However, malignant tumors arising from superficial peritoneal endometriosis lesions or DIEs are rare and standard therapy has not yet been established [ 6 9 ]. Hence, endometriosis can be malignant not only in the ovarian endometrioma but also in extra-gonadal endometriosis; nevertheless, there have been few reports of malignant tumors occurring as metachronous tumors in these endometriosis lesions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most malignant tumors arising from endometriosis are derived from the ovarian endometrioma. However, malignant tumors arising from super cial peritoneal endometriosis lesions or DIEs are rare and standard therapy has not yet been established [6][7][8][9]. Hence, endometriosis can be malignant not only in the ovarian endometrioma but also in extra-gonadal endometriosis; nevertheless, there have been few reports of malignant tumors occurring as metachronous tumors in these endometriosis lesions [10].…”
Section: Introductionmentioning
confidence: 99%